SAT0228 High Doses of Alfacalcidol or Prednisone Combined with Basic Therapy – are There Some More Advantages for Patients with Active Rheumatoid Arthritis?. (9th June 2015) - Simic Pasalic, K.; Zivanovic Radnic, T.; Sefik Bukilica, M.; Andjelkovic, A.; Damjanov, N.; Vojinovic, J.
Abstract : Background: The discovery of vitamin D receptor (VDR) in immune cells and the fact that some of these cells produce D hormone, indicated its antiinflammatory and immunoregulatory properties. Alfacalcidol is a VDR agonist. Objectives: To investigate the clinical effect of adding high doses of alfacalcidol or prednisone in patients with active rheumatoid arthritis (RA), to standard basic therapy Methods: The study which was approved by the Ethics Committee and the Drugs Agency and included active RA patients from the Rheumatology Institute in Belgrade, on standard prior methotrexate (MTX) use, for more than 3 months. After signing a consent for participation, demographic and clinical data were collected, disease activity (DAS 28), functional status (HAQ questionnaire), muscle function (timed up and go test -TUG and six minutes walk test- 6MWT) and quality of life (SF36 questionnaire) were assessed. Patients were randomly assigned to receive three-months treatment of 1 μg, 2μg, 3μg alfacalcidol or prednisone 20mg orally daily, with background MTX. They were monthly followed for clinical and laboratory findings, as well as adverse events (AE). At the end of treatment period, all tests were repeated and compared with the baseline ones. Statistical analysis was performed using the SPSS package. Results: Out of 67 pts, who were comparable, 39 were females, average age 56, 36 years, disease duration 7, 65 years, DAS28 5, 6, HAQ 0, 58, MTX dose 15, 48mg/weekly, serum 25(OH)D3 level 31.5 ng/ml. After 12 weeks of treatment, all four treatment arms significantly reduced DAS 28 (5, 6 vs 4, 4), HAQ (0, 58 vs 0, 4), improved PSC QoL (36, 39 vs 38, 9), 6MWT (404, 5 vs 464 m) ( p =0, 01, 0, 03 and 0, 001 respectively), while patients receiving alfacalcidol (N=51) also improved TUG (7, 26 vs 6, 69s), MCS QoL (48, 1 vs 50, 57), serum levels of HDL cholesterol (1, 5 vs 1, 62 mmol/l, p =0, 006). Serum levels of 25(OH)D3 in prednisone users (N=16) significantly decreased (37, 02 vs 21, 93 ng/ml, p =0, 000). Multiple comparison showed that alfacalcidol 2mg treated pts (N=19) improved DAS28, HAQ, PCS and MCS QoL significantly better than others ( p <0.05). Urinary calcium significantly increased in alfacalcidol treated ones, yet not exceeding URL (0, 156 vs 0, 28 g/dU, p =0, 001). Conclusions: Three months treatment with high doses of alfacalcidol in vitamin D replete active RA patients, led to improvement of disease activity, functional status, PCSQoL comparable to prednisone use, but also improved MCSQoL, muscle function and serum levels of HDL cholesterol, while preserving serum levels of 25(OH)D3. Disclosure of Interest: None declared